KARAKTERISTIK MUTU MIKROBIOLOGIS IKAN PINEKUHE KABUPATEN KEPULAUAN SANGIHE [Microbiological Quality Characteristics Of Fish Pinekuhe From Sangihe Regency] - Palawe, Jaka F.P.; Suwetja, I Ketut; Mandey, Lucia C. (Pascasarjana Unsrat, 2014)
Pinekuhe fish is one of the smoked fish products in Sangihe regency Pinekuhe made â€‹â€‹from fish Decapterus spp. This study aims to determine the microbiological quality characteristics of fish Pinekuhe. That is Total Plate Count (TPC), Escherichia coli, Salmonella, and Total Fungi. Microbiological test results TPC(Total Plate Count) showed that the fish pinekuhe quality that are above the maximum value of SNI, TPC Maximum 1.0 x 105 colonies/gra . The test showed salmonella and Escherichia coli in accordance with SNI. While for the fungi (mold) analyst, contamination found in fish Pinekuhe. Analysis of variance TPC (Total Plate Count) shows that there is a real difference where the District Manganitu and District Tahuna have higher levels of contamination, that is 1.633 x 105 and 1.567 x 105 when compared of District North Tabukan and District Middle Tabukan, that is 1.367 x 105 and 1.3 x 105. Meanwhile, analysis of variance Escherichia coli and total fungi did not show significant differences. Â Keywords : Pinekuhe, smoked fish, Sangihe Regency.